Museums and communities -The politics of public culture - Karp, Ivan (The American Association of Museums, 2020)
The essays in this volume were presented at a conference entitled Museums and Communities, held at the International Center of the Smithsonian Institution 2 1 -2 3 March 1990. Museums and Communities was the second of two conferences on the presentation and interpretation o f cultural diversity in museums. Proceedings of the first conference appear in Ivan Karp and Steven D. Lavine, eds., E xhibiting Cultures: The Poetics and Politics o f M useum Display (Washington, D.C.: Smithsonian Institution Press, 1991). Both conferences were sponsored by the Rockefeller Foundation and, at the Smithsonian, by the International Directorate, the Offices of the Assistant Secretaries for Museums and Research, and the National Museum of Natural History and its Department of Anthropology.